The November 10 Museum as a Space for Representing Surabaya’s Local Cultural Identity - Diva Pancah Rini; Yudiana Indriastuti (Jurnal Toursci, 2026)
Background. Museums serve not only as institutions for preserving historical heritage but also as spaces for representing local cultural identity. This study aims to analyze how Museum 10 November represents the local cultural identity of Surabaya as a historical tourism destination. A descriptive qualitative approach was employed through observation, in-depth interviews, and documentation involving museum managers and visitors. Aim. This study aims to analyze how Museum 10 November represents the local cultural identity of Surabaya through its historical narratives, collections, and exhibition displays. Methods. This study used a descriptive qualitative approach. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman interactive model. Results. The findings show that Museum 10 November represents Surabaya's local cultural identity through narratives of heroism, the values of Arek Suroboyo, cultural diversity, historical collections, and exhibition displays that strengthen visitors' understanding of the city's history and local identity. Conclusions. The study concludes that Museum 10 November functions as a medium for representing Surabaya's local cultural identity and contributes to strengthening cultural awareness through historical tourism experiences.